Clinical and radiological characteristics of patients with plantar fasciitis - A. P. Anischenko; S. I. Dzhadayev; A. V. Dzhadayeva; V. V. Inanov; M. V. Kovrizhnyh (Спортивная медицина: наука и практика, 2023)
Aim: to study the clinical and radiological parameters of patients with plantar fasciitis.Materials and methods: the study involved 91 patients with plantar fasciitis, 73 (80.2%) women, 18 (19.8%) men. The mean age of the patients was 53.42 ± 9.16 years, disease duration was 30.32 ± 8.06 days, BMI was 24.75 ± 4.55 kg/m2. Patients underwent history taking, pain level and quality of life were assessed using the visual analogue scale, the SF-36 questionnaire and the AOFAS scale. The functional state of the feet was assessed using plantoscopy, Y-balance test, Friedland index. X-ray parameters were assessed using magnetic resonance imaging.Results: the disease is common among women aged 51 to 60 years. In 100% of cases, there is no traumatic etiological factor, 42.9% of the subjects note an increase in body weight as the cause, 35.2% – the relationship of the onset of pain with wearing flat shoes; men are more likely to associate the onset of symptoms with an increase in physical activity (83.3%). Subjective sensation of pain on the VAS does not depend on gender (p = 0.280), age (p = 0.509), disease duration (p = 0.371), BMI (p = 0.974). X-ray parameters of patients are characterized in 49.5% by the absence of heel exostosis, in other cases, the development of a heel spur is more typical for women (p = 0.019), its length does not depend on the duration of the disease (p = 0.845), age (p = 0.054), BMI (p = 0.196), lifestyle (p = 0.324) and does not correlate with the severity of pain (p = 0.691). The level of pain is directly proportional to the thickness of the plantar fascia (p < 0.001, ρ = 0.459). Calcaneal edema is observed in 14.3 % of patients, soft tissue edema — in 18.7 %; there was no relationship between calcaneal edema (p = 0.604) and soft tissue edema (p = 0.541) with the severity of pain, and calcaneal edema directly correlates with BMI (p = 0.029).Conclusion: These studies suggest that among the predictors of the development of plantar fasciitis, the most significant are female gender, overweight, wearing flat shoes, and the disease itself is not always a consequence of the development of a heel spur.